Characterization of pneumatic muscles and their use for the position control of a mechatronic finger. (April 2017) - Oliver-Salazar, M.A.; Szwedowicz-Wasik, D.; Blanco-Ortega, A.; Aguilar-Acevedo, F.; Ruiz-González, R.
Highlights: Methodology to calculate pneumatic muscles sizes in terms of working physical parameters. Design and construction of a 4°-of-freedom finger driven by pneumatic muscles. Functional and anthropomorphic finger with smooth and precise movements. dsPIC-based electronic board and graphic user interface conforming a portable stand-alone system. Possible applications in robotic-based programmable rehabilitation therapies for patients. Abstract: The objective of this work is to present a methodology to construct pneumatic muscles with length sizes depending on the operation parameters such as working pressure, contraction and force and without the need of complicated mathematical models. To validate the convenience of the proposed methodology, a mechatronic finger driven by pairs of pneumatic muscles in antagonist operation reproducing similar movements to those of a human finger was developed and tested. This four-degrees-of-freedom mechatronic finger consists of a proximal phalanx with a ball-and- socket joint to allow flection-extension and adduction-abduction movements; a medial phalanx for flection-extension movements and a distal phalanx also for flection-extension movements. Inflation/deflation for each muscle is achieved by the use of proportional-type valves. To control the movement of each constituent joint the direct and inverse kinematic equations were obtained and PID-type controllers were tuned. Measurement of the angular position for each joint was obtained by the use of Hall-effect sensors. For the signal conditioning and processing a dsPIC-based, autonomous electronic board and a graphic user interface were developed to conform a portable stand-alone system. The finger presents two convenient features; functionality and anthropomorphism. Simulation tests including the kinematic model were carried out and experimental tests with the prototype were performed getting converging results. The achieved finger movements with and without a load mass were smooth and precise, justifying the convenience of using the proposed method for the dimensioning of the muscles sizes. Further work is the design of a mechatronic hand based on pneumatic fingers of this sort. By presenting and testing this methodology it is intended that this work contributes to the claim of different authors regarding the benefits of using pneumatic muscles as reliable bio-inspired actuators in applications such as orthopaedic rehabilitation equipment and in the design of wearable robotic devices for knee motions.